An option embedded novel military service system based on cognitive bias theories - Hyoung Goo Kang; Byungsuk Han (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2020)
The purpose of this study is to hypothesize that cognitive biases such as nostalgia, rosy retrospection, overconfidence, fading-affect bias and prospect theory affect how to serve in the military. The behaviors of those expecting military service and those who have completed the service differ significantly in evaluating the self and social value of the human capital during the military service. This difference corresponds to the predictions of the cognitive-bias literature. The authors test propositions in option framework. This study's experimental design proposes a novel military system, a hybrid of conscription and voluntary systems. This study's results are consistent with the hypothesis, option theory and behavioral economics literature.
Keywords: G13; G41; 330; Cognitive bias; Option; Military service; Conscription; Irrational behavior